Fuzzy Sliding Mode Controller for Induction Machine Feed by Three Level Inverter - Lakhdari Lahcen; B. Bouchiba (Institute of Advanced Engineering and Science, 2018)
In this paper, using synthesis of a hybrid control is applied to the speed of an induction motor feed by three-level inverter. Based on the combination of the fuzzy logic and the sliding mode approach, this method has the advantage of combining the performances of the two types of controllers. The fuzzy logic confers a very appreciable flexibility to the reasoning which uses and makes it possible to take into account Imprecisions and uncertainties, The sliding mode is a controller for nonlinear systems with non-constant parameters; it leads to precision and robustness, and allows solving problems obtained by conventional control laws. To lift the stresses of external disturbance and makes the system more performing and more robust, the two controllers of fuzzy logic and sliding mode are combined.